Pengembangan Media Permainan Ular Tangga untuk Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran Bahasa Indonesia - Wangi Netralli Lase; Anaria Zalukhu; Stanislaus Rahasia Zalukhu; Noveri Amal Jaya Harefa (Journal on Education, 2023)
The learning process that occurs almost every day certainly needs the creativity of an educator so that students are not bored while learning. Teaching media is one of the solutions in solving the problem because the media includes lessons delivered by the teacher is not understood but with the media can be understood. This research is a snakes and ladders media development research to increase student learning motivation. This research is a 3D media formed with colors and accompanied by questions for Class VII Students of SMP Negeri 7 Alasa. This research was conducted using the ADDIE development model, the subjects of this research were seventh grade students of SMP Negeri 7 Alasa. There are two data collection techniques carried out in this study, namely the effectiveness of media engineering and the feasibility of visual communication aspects obtained through learning outcomes, student responses to learning media; practicality, obtained from assessment instruments. The results showed that the average value of media engineering effectiveness was 93% which means "very feasible" and the feasibility of visual communication aspects obtained 89% which means "very feasible".